MINAT BELAJAR SISWA KELAS XI IPS DALAM MENGIKUTI PEMBELAJARAN PENJAS DI SMAN 1 KELAYANG KABUPATEN INDRAGIRI HULU - Yeni Enita; Ricky Fernando; Rices Jatra (Journal of Innovation Research and Knowledge, 2023)
The purpose of this research was to find out the Learning Interests of Class XI IPS Students in Following Physical Education Learning at SMAN 1 Kelayang, Indragiri Hulu Regency. The type of this research is descriptive quantitative with a survey type using a questionnaire as an instrument. The population in this study were students of class XI Social Sciences at SMAN 1 Kelayang, Indragiri Hulu Regency, with a total of 64 students. The sampling technique used is random sampling technique, namely taking members of the sample randomly. The data analysis technique used is to calculate the percentage value of the final questionnaire score. Based on the results of the research, the conclusions obtained in this study are: The learning interest of class XI IPS students in participating in physical education learning at SMAN 1 Kelayang, Indragiri Hulu Regency, is included in the value range of 61-80% or in the strong category with a percentage of 71.44%.